Clinical evaluation and management of dilated cardiomyopathy in dogs - Dhanya V Pai (Department of Clinical Veterinary Medicine, College of Veterinary and Animal Sciences, 2009)
Eight dogs presented with clinical signs suggestive of cardiac problems and later confirmed for DCM were utilised for the detailed treatment studies. Signalment, history, electrocardiography, radiography, echocardiography, haematology, serum biochemistry and response to treatment of enalapril @ 0.5 mg/kg bid, valsartan @ 2 mg/kg bid and lasilactone @ 2mg/kg bid orally were studied.